Studi Etnometodologi Islam untuk Mengupas Praktik Akuntansi Hutang - Thalib, Mohamad Anwar (Jurnal Akuntansi, Keuangan, dan Manajemen, 2023)
Purpose: This study explores debt accounting practices conditional on non-material values. Method: This study uses an Islamic paradigm, qualitative method, and Islamic ethnomethodological approach. There were five data analysis stages: charity, knowledge, faith, revelation information, and ihsan. Result: The study results show that there is a practice of debt accounting in the form of sources of debt funds obtained from friends and relatives. Debt funds are intended only to finance urgent needs. Debt repayment is performed through salary deductions and repayments assisted by the husband. The debt was recorded. This debt accounting practice requires non-material value in the form of responsibility. This value is reflected in the informants' actions, who only make loans when there is an urgent need, and the informants record the debts made and the date of payment of the debt. Limitation: A limitation of this research is that no documentation was found on the method of recording debt accounting by honorary teachers. Contribution: This study contributes to the literature by presenting the concept of debt accounting by honorary teachers, based on non-material values in the form of responsibility. Novelty: The novelty of this research lies in the results of this study, presenting the concept of debt accounting not limited to techniques and calculations, but conditions with non-material values.